2010
DOI: 10.1371/journal.pone.0012416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Botulinum Neurotoxin Type A Neutralizing Monoclonal Antibodies and Influence of Their Half-Lives on Therapeutic Activity

Abstract: Botulinum toxins, i.e. BoNT/A to/G, include the most toxic substances known. Since botulism is a potentially fatal neuroparalytic disease with possible use as a biowarfare weapon (Centers for Disease Control and Prevention category A bioterrorism agent), intensive efforts are being made to develop vaccines or neutralizing antibodies. The use of active fragments from non-human immunoglobulins (F(ab')2, Fab', scFv), chemically modified or not, may avoid side effects, but also largely modify the in vivo half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
(38 reference statements)
3
37
0
Order By: Relevance
“…Intact MAbs and their F(ab′) 2 fragments were administered in equimolar concentrations in respect to their binding titer to rule out any bias as a result of differences in functional binding. Our observations are not entirely consistent with results reported by Mazuet et al, who conducted a BoNT toxicity study with two MAbs; one F(ab′) 2 fragment exerted less protection in mice, while the other F(ab′) 2 fragment retained the neutralization efficacy of its intact IgG, despite the clearly longer half-lives for both intact IgGs in the blood [29]. Interestingly, the MAb that was not affected by the Fc fragment deletion in the Mazuet et al study displayed a neutralization activity that was comparable to that of a PAb preparation [29].…”
Section: Discussionsupporting
confidence: 59%
“…Intact MAbs and their F(ab′) 2 fragments were administered in equimolar concentrations in respect to their binding titer to rule out any bias as a result of differences in functional binding. Our observations are not entirely consistent with results reported by Mazuet et al, who conducted a BoNT toxicity study with two MAbs; one F(ab′) 2 fragment exerted less protection in mice, while the other F(ab′) 2 fragment retained the neutralization efficacy of its intact IgG, despite the clearly longer half-lives for both intact IgGs in the blood [29]. Interestingly, the MAb that was not affected by the Fc fragment deletion in the Mazuet et al study displayed a neutralization activity that was comparable to that of a PAb preparation [29].…”
Section: Discussionsupporting
confidence: 59%
“…In addition, multilocus sequence type (MLST) profiling analysis showed that the A3 strain is clearly distinguished from other subtype A strains (15). Of considerable interest is that BoNT/A3 was found to be less effectively neutralized by antiBoNT/A1 antibody (22). However, the purification of BoNT/A3 presented considerable challenges.…”
Section: Discussionmentioning
confidence: 99%
“…BoNT/A3 is not effectively neutralized by antiBoNT/A1 antibodies (J. Marks, personal communication; 22), which indicates that certain epitopes responsible for neutralization are different between BoNT/A1 and BoNT/A3. This difference in immunogenicity leads to the possibility that BoNT/A3 could potentially replace BoNT/A1 for those patients who have developed neutralizing antibodies to BoNT/A1 due to repeated treatments or immunization with BoNT/A1.…”
mentioning
confidence: 99%
“…Similar experiments investigating symptoms of intoxication have not been conducted for other subtypes. Additionally, various investigators have shown differences in the ability of monoclonal and polyclonal antibodies to bind to or neutralize various subtypes within the same serotype (23,(25)(26)(27).…”
mentioning
confidence: 99%